Parupama; Nasehat yang Menghibur - Syamsurijal Syamsurijal (Jurnal Lektur Keagamaan, 2017)
Movement of literacy in the community, making oral tradition has lost own place. Folklore and fairy tales told through oral began to be replaced by comics, movies on television and writing through gadgets. In local communities, the oral tradition is still an important means of informing  messages. One of the living oral traditions and the media to express criticism is Parupama in South Sulawesi. This paper explains  how this parupama tradition is used by community to convey advice, messages and criticism through jokes. Advice and criticism is channeled through in an entertaining way. The data in this paper were obtained through qualitative research in two places, namely Tanah Toa Kajang and Tamaona village located in Bulukumba district, South Sulawesi.Key word: Message, Oral tradition, Criticism, Parupama Gerakan literasi di tengah masyarakat telah membuat tradisi lisan kehilangan tempat. Cerita rakyat dan dongeng yang disampaikan melalui lisan mulai digantikan dengan komik, film di televisi dan tulisan melalui gadget. Padahal di masyarakat lokal sendiri, tradisi lisan masih menjadi sarana penyampaian pesan yang penting. Salah satu tradisi lisan yang masih hidup dan menjadi media menyampaikan nasehat adalah Parupama yang hidup dalam masyarakat Sulawesi Selatan. Tulisan ini menggambarkan bagaimana tradisi Parupama ini digunakan oleh masyarakat untuk menyampaikan nasehat, pesan dan kritikan melalui lelucon. Nasehat dan kritikan disalurkan dengan cara menghibur. Data dalam tulisan ini didapatkan melalui penelitian kualitatif di dua tempat, yaitu desa Tanah Toa Kajang dan desa Tamaona, berada di kabupaten Bulukumba, Sulawesi-selatan.   Kata Kunci: Pesan, tradisi lisan, kritik, parupama